Model of Our Trial: A Construct from the Systematic Review in the Glorious Qur’an, Sunnah and Published Articles in Biomedical Sciences - Abdillah Mussa Kitota (LECTURES: Journal of Islamic and Education Studies, 2024)
All over the world, values of people are increasingly deteriorating due to the modern life systems caused by ongoing advancement of science and technologies. This systematic study was conducted to analyze the nature of our trial by integrating the exposition of the Qur'an, Ahadith, and signs of Allah (S.W.T) in ourselves revealed to us through biomedical sciences. Data were collected from Qur’an and six canonical books of ahadith collection of Ahlu Sunna Waljama'a and published studies screened from MEDLINE, EMBASE & SCOPUS. Qur’anic data were analyzed by Thematic Approach [Uslub Tafsir Al-Maudhu’i] and Synoptic Approach [Uslub Tafsir Ijmali]. The findings show that our trial is governed by four things: ruh, heart, ears, and eyes. The ruh is an agent with heavenly origin installed with a desire to remember Allah (S.W.T); while the heart, ears, and eyes have an earthly origin, created from dust and water. However, despite its earthly origin, the heart is a controlling center of our trial; because it occupies the midst position; connecting in terms of communication, between the ruh and body. The ruh stress its desire to the body via the heart, and the information about the words and deeds of the body are communicated to the ruh via the heart; while the main gates of information to the heart are ears and eyes. The quality of the ruh will depend on quantity and quality of the information sent to the heart. These findings may add value to the existing efforts of dealing with moral deterioration.